DIELECTRIC PROTECTION OF ALUMINUM ALLOYS OF DIAMOND WHEEL FRAMEWORKS BY PLASMA-ELECTROLYTIC COATINGS WITH FORMING IN GALVANOSTATIC MODE - Elena SEVIDOVA; Yury GUTSALENKO; Cătălin IANCU; Valeria SUBBOTINA; Oleh VOLKOV (Fiabilitate şi Durabilitate)
The study was carried out within the framework of the field of technological solutions for local electrical insulating coatings of the tool of highly efficient processing technologies with the introduction of electric discharge energy into the cutting zone to maintain the performance of grinding wheels with a diamond-metal composition of the working part. The development of plasma electrolyte oxidation of aluminum alloys with the aim of using the dielectric properties of coatings is presented. Investigations of oxide coatings formed by the anode galvanostatic regime in alkali-silicate solutions are presented and discussed. The data on the roughness, radiology and dielectric properties of the coatings are used for joint consideration.